2022
DOI: 10.23917/jramathedu.v7i1.15740
|View full text |Cite
|
Sign up to set email alerts
|

Tracing proof schemes: some patterns and new perspectives

Abstract: The aim of this paper is to review some studies conducted with different learning areas in which the schemes of different participants emerge. Also it is about to show how mathematical proofs are handled in these studies by considering Harel and Sowder's classification of proof schemes with specific examples. As a result, it was seen that the examined studies were addressed in the learning areas of Analysis, Geometry, Algebra, Linear Algebra, Elementary Number Theory, Probability, Combinatorics, and MIX. Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the literature about mathematics, there is a formal establishment of the concept of proof, and it is indicated that the proving process is an integral part of the curriculum in terms of emphasizing the relationships between the learning areas (Yilmaz Akkurt & Durmus, 2022). There are some specific stages in approaching a problem and getting to the proof.…”
Section: Theoretical Issuesmentioning
confidence: 99%
“…In the literature about mathematics, there is a formal establishment of the concept of proof, and it is indicated that the proving process is an integral part of the curriculum in terms of emphasizing the relationships between the learning areas (Yilmaz Akkurt & Durmus, 2022). There are some specific stages in approaching a problem and getting to the proof.…”
Section: Theoretical Issuesmentioning
confidence: 99%
“…Saeedullah (2021) also developed an instrument to measure mathematical reasoning in senior high school using five constructs of mathematical reasoning, such as mathematical inductive reasoning, deductive reasoning, generalization, adaptive reasoning, and problem-solving. In recent years, research on the assessment of mathematical reasoning and proof has been more on developing instruments that focus on revealing reasoning abilities, especially for mathematics students or teachers (Stylianides & Stylianides, 2009;Akkurt & Durmus, 2022;Sari, 2017). However, there is yet an instrument that reveals both of reasoning and proof ability.…”
Section: Introductionmentioning
confidence: 99%